2012
DOI: 10.1007/s10565-011-9208-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary human hepatocytes, HepG2 cells, and HepaRG cells at the mRNA level and CYP activity in response to inducers and their predictivity for the detection of human hepatotoxins

Abstract: In the pharmaceutical industry, improving the early detection of drug-induced hepatotoxicity is essential as it is one of the most important reasons for attrition of candidate drugs during the later stages of drug development. The first objective of this study was to better characterize different cellular models (i.e., HepG2, HepaRG cells, and fresh primary human hepatocytes) at the gene expression level and analyze their metabolic cytochrome P450 capabilities. The cellular models were exposed to three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
406
1
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(436 citation statements)
references
References 45 publications
18
406
1
11
Order By: Relevance
“…Since the HepaRG cell line was first described in 2002, many reports [33,34] have appeared that have described its unique features. These include the ability to differentiate towards both hepatocyte-like and biliary-like cells and the ability to stably express a range of important hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Since the HepaRG cell line was first described in 2002, many reports [33,34] have appeared that have described its unique features. These include the ability to differentiate towards both hepatocyte-like and biliary-like cells and the ability to stably express a range of important hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…To reach phenotypic maturity, HepaRG cells grow to confluence and differentiate over 4 weeks (from progenitor cells) into cocultures of hepatocyte-like and cholangiocyte-like cells (Gripon et al, 2002). Since this model was discovered, many studies have shown that freshly differentiated HepaRG cultures exhibit cellular interactions, drug metabolism/transport, and drug induction responsiveness comparable to PHH cultures (Grime et al, 2010;McGill et al, 2011;Gerets et al, 2012;Le Vee et al, 2013;Szabo et al, 2013). A cryopreserved format of differentiated HepaRG cells (cryo-HepaRG) has recently become available, improving the global availability and experimental flexibility of this model.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies using primary-cultured human hepatocytes or human immortalized cells have been reported for evaluating DILI, using flutamide (Gerets et al, 2012), diclofenac (Bort et al, 1999), isoniazid (Wang et al, 2002) or chlorpromazine (Gerets et al, 2012) as model drugs. These studies all utilized the IC 50 value of albumin secretion as a toxicity parameter, and all of them yielded values similar to or greater than our IC 50 value.…”
Section: Discussionmentioning
confidence: 99%